Recent Advances in the Application of Mesenchymal Stem Cell-Derived Exosomes for Cardiovascular and Neurodegenerative Disease Therapies - Zhimin Yang; Yanyu Li; Zihua Wang (MDPI AG, 2022)
Exosomes are naturally occurring nanoscale vesicles that are released and received by almost all cells in the body. Exosomes can be transferred between cells and contain various molecular constitutes closely related to their origin and function, including proteins, lipids, and RNAs. The importance of exosomes in cellular communication makes them important vectors for delivering a variety of drugs throughout the body. Exosomes are ubiquitous in the circulatory system and can reach the site of injury or disease through a variety of biological barriers. Due to its unique structure and rich inclusions, it can be used for the diagnosis and treatment of diseases. Mesenchymal stem-cell-derived exosomes (MSCs-Exo) inherit the physiological functions of MSCs, including repairing and regenerating tissues, suppressing inflammatory responses, and regulating the body's immunity; therefore, MSCs-Exo can be used as a natural drug delivery carrier with therapeutic effects, and has been increasingly used in the treatment of cardiovascular diseases and neurodegenerative diseases. Here, we summarize the research progress of MSCs-Exo as drug delivery vectors and their application for various drug deliveries, providing ideas and references for the study of MSCs-Exo in recent years.